Hurried child syndrome: A narrative review - Agrawal , Amit; Sharma, Shweta; Shrivastava, Jyotshna (Indian Journal of Child Health, 2022)
When a child's parents expect him or her to perform much above his or her mental, social, or emotional capacity, the condition known as "Hurried Child Syndrome (HCS)" develops. In today’s world, parents overbook their kids' calendars, push them to do well in school, and demand that they behave and react just like little adults. The current situation of trade is one of the other considerations. We live in a time-restricted culture where the emphasis is primarily on speed, instant gratification, fast meals, etc. This eventually leads to parenting a hurried child. The current research review focuses on the causes, consequences, and preventative approaches of the resulting HCS.